“Caracterización fenotípica de ecotipos de frijol común (phaseolus vulgaris) en el fundo aucaloma - Lamas” - Amaringo Grández, Shirley (2015)
In the province of San Martin, there are beans overa century the jungle settler has preservad from generation to generation whose characteristics are different from each other: color, shape, grain size, growth habit, but there are no reports of the characteristics and agronomic management of the huasca ecotypes allpa, pajatino and ahuisho. Tobacco of Peru introduced a variety of Juan Guerra 2003, known as "reclinea" by farmers being susceptible to cromista Phytophthora phaseolli. In this research four ecotypes originating from the forest and introduced ecotype (kidney network) by morphological and physiological characteristics were evaluated, looking for basic information to farmers who grow beans and improve their agronomic management. Obtenindo so: Ahuisho reportad the highest average 5040.4 kg ha-1 yield, statistically outperforming Pajatino, Allpa, Eed Kidney and Huasca ecotypes who reportad average 4017.3 kg ha-1, 2677.2 kg.ha- 1 2643.2 and 2395.7 kg ha-1 kg ha- 1 yield respectively. The T1 has the following characteristics: predominant color = purple cotyledon, predominant color of the ribs of the primary = green sheets, standard color= purple flower, growth habit = determinate bush, talo color= green, = normal green leaves, pale color = green immature pods ripe color = cream pods, pods in harvest color = cream predominate profile sheath = straight, seed color = pink, seed shape = arriñonada curved in the opposite straight side. Keywords: huasca, allpa, pajatino and ahuisho